2019
DOI: 10.1097/cm9.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of broad-spectrum antibiotics on bacterial translocation in burned or septic rats

Abstract: Background: Antibiotics are frequently used to treat critically ill patients, and its use is often accompanied by intestinal dysbiosis that might further lead to bacterial translocation (BT). Nevertheless, studies on the relationship between antibiotic therapy and BT are rare. In the present study, we investigated the effect of broad-spectrum antibiotics on BT in an experimental rat model of burn or sepsis injury. Methods: The septic rat model was simulated by a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Currently, BT is an immune deficiency that may be acquired or caused by genetic susceptibility and functions in tandem as a pathophysiological perpetrator for most cirrhosis-related bacterial infections. 29 BT exists in healthy conditions but is elevated in cirrhosis, and therefore is considered to be pathological BT. Nevertheless, studies on the relationship between antibiotic therapy and BT are rare, but in a study by Wen et al 29 conducted on the frequent use of antibiotics and the effect of broad-spectrum antibiotics on BT in experimental rat models of burn or sepsis injury, it was observed that broad-spectrum antibiotics promote BT in burned rats but prevent BT in septic rats, thereby preventing the spread of BT to distant organs, such as the liver and lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, BT is an immune deficiency that may be acquired or caused by genetic susceptibility and functions in tandem as a pathophysiological perpetrator for most cirrhosis-related bacterial infections. 29 BT exists in healthy conditions but is elevated in cirrhosis, and therefore is considered to be pathological BT. Nevertheless, studies on the relationship between antibiotic therapy and BT are rare, but in a study by Wen et al 29 conducted on the frequent use of antibiotics and the effect of broad-spectrum antibiotics on BT in experimental rat models of burn or sepsis injury, it was observed that broad-spectrum antibiotics promote BT in burned rats but prevent BT in septic rats, thereby preventing the spread of BT to distant organs, such as the liver and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…29 BT exists in healthy conditions but is elevated in cirrhosis, and therefore is considered to be pathological BT. Nevertheless, studies on the relationship between antibiotic therapy and BT are rare, but in a study by Wen et al 29 conducted on the frequent use of antibiotics and the effect of broad-spectrum antibiotics on BT in experimental rat models of burn or sepsis injury, it was observed that broad-spectrum antibiotics promote BT in burned rats but prevent BT in septic rats, thereby preventing the spread of BT to distant organs, such as the liver and lungs. In agreement with those findings, our study outcomes clearly indicated that early initiation of AEA therapy led to a higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are reported to affect the inflammatory process and ameliorate intestinal microcirculation in sepsis [107]. It was recently demonstrated that broad-spectrum antibiotics prevent BT to distant organs such as the liver and lungs in septic rats [108]. There is, however, evidence that broad-spectrum antibiotics can lead to an imbalance in the intestinal micro ecological environment, promote BT in sepsis, and cause drug resistance and pathogenicity, especially when MODS develops [109].…”
Section: Selective Elimination Of Pathogenic Bacteriamentioning
confidence: 99%
“…Sepsis is a syndrome caused by uncontrolled inflammation in response to infection, which could lead to lifethreatening organ damage and dysfunction, and even be fatal. [1][2][3] Sepsis-induced intestinal injury promotes the translocation of intestinal bacteria and toxins, [4,5] which exacerbates the systemic inflammatory response and accelerates the pathological process of sepsis. [5] Liu et al [6] have shown that approximately half of all patients with sepsis develop gastrointestinal dysfunction, and the case fatality rate for patients with sepsis doubles when intestinal dysfunction occurs compared with that for patients without intestinal dysfunction.…”
Section: Introductionmentioning
confidence: 99%